RETRACTED ARTICLE: Target receptor identification and subsequent treatment of resected brain tumors with encapsulated and engineered allogeneic stem cells - Deepak Bhere; Sung Hugh Choi; Pim van de Donk; David Hope; Kiki Gortzak; Amina Kunnummal; Jasneet Khalsa; Esther Revai Lechtich; Clemens Reinshagen; Victoria Leon; Nabil Nissar; Wenya Linda Bi; et al. (Nature Communications)
Abstract Cellular therapies offer a promising therapeutic strategy for the highly malignant brain tumor, glioblastoma (GBM). However, their clinical translation is limited by the lack of effective target identification and stringent testing in pre-clinical models that replicate standard treatment in GBM patients. In this study, we show the detection of cell surface death receptor (DR) target on CD146-enriched circulating tumor cells (CTC) captured from the blood of mice bearing GBM and patients diagnosed with GBM. Next, we developed allogeneic “off-the-shelf” clinical-grade bifunctional mesenchymal stem cells (MSCBif) expressing DR-targeted ligand and a safety kill switch. We show that biodegradable hydrogel encapsulated MSCBif (EnMSCBif) has a profound therapeutic efficacy in mice bearing patient-derived invasive, primary and recurrent GBM tumors following surgical resection. Activation of the kill switch enhances the efficacy of MSCBif and results in their elimination post-tumor treatment which can be tracked by positron emission tomography (PET) imaging. This study establishes a foundation towards a clinical trial of EnMSCBif in primary and recurrent GBM patients.